Peningkatan Penggunaan Antibiotik Secara Bijak Melalui Intervensi Alih Pengetahuan Untuk Merubah Persepsi Masyarakat di Kabupaten Banyumas - Dwi Utami Anjarwati; Fajar Wahyu Pribadi; Idsap Peramiarti (Universitas Mathla'ul Anwar Banten, 2017)
IMPROVED USE OF ANTIBIOTIC BY USING TRANSFER OF KNOWLEDGE INTERVENTIONS TO CHANGE THE COMMUNITY PERCEPTION IN BANYUMAS DISTRICT. The use of antibiotics without indication by the medical community and the community became the trigger factor of increasing the incidence of antibiotic resistance in Indonesia. Meanwhile by 20150 antibiotic resistance is predictedto be the leading cause of death in the world. Community devotion was aimed at improving the understanding of society so that that is a change of perception about the use of antibiotic wisely. The target respondents of devotion consists of member of the family welfare empowerment group (PKK). A seriaes of activities undertaken were pre and post test to measure respondents' understanding of antibiotic use before and after intervention in the transfer of knowledge. The questionnaire used previously tested its validity by Pearson product moment test and its reliability by Alpha-Cronbach. The Sharpening of material obtained in knowledge transfer was done with role play and discussion. The result of T test analysis to score of quesionnaire before and after knowledge transfer showed significant p value (p = 0,049). The conclusion was that the transfer of knowledge can change the perception of PKK members about the wise use of antibiotics.